2022
DOI: 10.1186/s12863-022-01096-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolism-related genes for predicting peritoneal metastasis in patients with gastric cancer

Abstract: Objective The reprogramming of metabolism is an important factor in the metastatic process of cancer. In our study, we intended to investigate the predictive value of metabolism-related genes (MRGs) in recurrent gastric cancer (GC) patients with peritoneal metastasis. Methods The sequencing data of mRNA of GC patients were obtained from Asian Cancer Research Group (ACRG) and the GEO databases (GSE53276). The differentially expressed MRGs (DE-MRGs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…12 The ACRG gene expression profiling data were obtained from the NCBI Gene Expression Omnibus (GSE62254) and the gene somatic mutation and clinical data were downloaded from the literature. 11 The TCGA-STAD dataset was downloaded from the GDC data portal (https://portal.gdc.cancer.gov/). MIG gene lists were obtained through the Kyoto Encyclopedia of Genes and Genomes (KEGG) PATHWAY Database (http://software.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The ACRG gene expression profiling data were obtained from the NCBI Gene Expression Omnibus (GSE62254) and the gene somatic mutation and clinical data were downloaded from the literature. 11 The TCGA-STAD dataset was downloaded from the GDC data portal (https://portal.gdc.cancer.gov/). MIG gene lists were obtained through the Kyoto Encyclopedia of Genes and Genomes (KEGG) PATHWAY Database (http://software.…”
Section: Data Collectionmentioning
confidence: 99%
“…9 Several studies have demonstrated the potential of immune and metabolic gene-based signatures for predicting GC prognosis and guiding treatment decisions. 10,11 However, challenges remain in the development and validation of these signatures, such as the need for large, high-quality datasets and the identification of robust biomarkers that can be translated into the clinic. In this paper, we will review recent advances in the construction of immune and metabolic gene-based prognosis signatures in GC and discuss their potential clinical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCPM has been linked to various clinicopathological characteristics, genetic mutations and molecular signatures. [8][9][10] However, the usefulness of these histopathology and molecular classifications in clinical practice remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended to adopt a combination of systemic therapy and peritoneal‐directed treatment strategies, such as intraperitoneal chemotherapy, which have demonstrated an encouraging trend towards improved disease outcomes. GCPM has been linked to various clinicopathological characteristics, genetic mutations and molecular signatures 8–10 . However, the usefulness of these histopathology and molecular classifications in clinical practice remains limited.…”
Section: Introductionmentioning
confidence: 99%